Analisis Tingkat Kepuasan Masyarakat terhadap Penerapan Blue Sistem pada Pelayanan Pengujian Kendaraan Bermotor di Kota Denpasar - I Made Endra Lesmana Putra; Gede Agus Dian Maha Yoga (UNHI Press, 2022)
This study was conducted with the aim of evaluating the level of public satisfaction with the implementation of the vehicle test book public service by obtaining Evidence of Passing the Electronic Test as a substitute for the vehicle test book at the motor vehicle testing, Denpasar City transportation service. There are two variables used, namely the level of conformity of service expectations and the level of conformity of service performance. The servqual dimension used to assess customer satisfaction consists of tangible (tangible), reliability (reliability), responsiveness (responsiveness), assurance (certainty), and empathy (empathy). The results showed the average satisfaction of tangible dimensions (86.86), reliability (81.62), responsiveness (85.94), assurance (82.17), and empathy (86.73). The comparison between the level of conformity of expectations with the suitability of performance is 84.66 points which can be interpreted as